Corrigendum to “Wavelet based numerical approach of non-classical moving boundary problem with convection effect and variable latent heat under the most generalized boundary conditions” [Eur. J. Mech. B Fluids 87 (2021) 1–11] (European Journal of Mechanics / B Fluids (2021) 87 (1–11), (S0997754621000030), (10.1016/j.euromechflu.2021.01.003)) - Jitendra; Rai K.N.; Singh J. (My University, 2025)
In this paper, there is a correction in the nomenclature of the following nonlinear thermal coefficients which are mentioned below 1. [Formula presented] Coefficient of latent heat, [Formula presented]. 2. [Formula presented] Coefficient of heat flux, [Formula presented]. 3. [Formula presented] Constant of heat transfer coefficient, [Formula presented]. 4. [Formula presented] Physical quantity [Formula presented]. 5. [Formula presented] Stefan like number [Formula presented]. We have just used these nonlinear thermal coefficients as a reference value. The purpose of these nonlinear thermal coefficients is for numerical computation like reference values in our paper. All the analysis in our paper using different nonlinear thermal coefficients are shown graphically. The rest part of the paper remains unchanged. © 2021 Elsevier Masson SAS